Green production of a novel sorbent from kaolin for capturing gaseous PbCl2 in a furnace - Zha, Jianrui; Huang, Yaji; Clough, Peter T.; Xia, Zhipeng; Zhu, Zhicheng; Fan, Conghui; Yu, Mengzhu; Yan, Yongliang; Cheng, Haoqiang (Elsevier, 2020)
The pollution of semi-volatile heavy metals is one of the key environmental risks for municipal solid waste incineration, and in-situ adsorption of metals within the furnace by mineral sorbents such as kaolin has been demonstrated as a promising emission control method. To lessen the consumption of sorbent, a novel material of amorphous silicate was produced from kaolin through pressurised hydrothermal treatment. Its performance of gaseous PbCl2 capture was tested in a fixed bed furnace and compared with unmodified kaolin and metakaolin. With increasing temperature, the adsorption rates for all sorbents declined due to higher saturated vapour pressure, while the partitions of residual form lead increased which indicated higher stability of heavy metals in the sorbent because of melting effect. The new sorbent with a larger surface area and reformed structure presented 26% more adsorption efficiency than raw kaolin at 900 °C, and increasing the modification pressure improved these properties. Additionally, the production of this high-temperature sorbent was relatively inexpensive, required little thermal energy and no chemicals to produce and no waste effluent was generated, thus being much cleaner than other modification methods.
Keywords: Kaolin; Adsorption; PbCl2; High temperature; Hydrothermal modification